ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK HOTEL DI KABUPATEN GIANYAR - Mahasena, Ida Bagus Putu; Wirama, Dewa Gede; Ratnadi, Ni Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.03.TAHUN 2017, 2017)
The purpose of this study is to determine the effects of distributive justice, quality of service, enforcement of tax penalties and moral obligation on hotel taxpayer compliance. The research was conducted in Gianyar Regency with owners or general managers of the hotel as respondents. The number of samples analyzed are 266 respondents, determined by proportionate stratified random sampling technique. Methods of data collection are questionnaire and documentation. The data analysis technique used is multiple linear regression. Results of the analysis shows that distributive justice has positive effect on tax compliance. Quality of service has positive effect on tax compliance. Enforcement of tax penalties has positive effect on tax compliance. Moral obligation has positive effect on tax compliance.
Keywords: compliance, fairness, quality of service, enforcement of tax penalties and moral obligation